Facial danger zones : staying safe with surgery, fillers, and non-invasive devices - Rohrich, Rod J.; Stuzin, James M.; Dayan, Erez; Ross, E. Victor; Tomasikiewicz, Amanda (Thieme, 2020)
"The goal of this book is three-fold: - Optimal knowledge of facial anatomy is germane to obtaining the best results and safe outcomes in facial aesthetic surgery. This is especially the case with the intricate anatomy of the facial nerve in facelift surgery as discussed by Dr. James Stuzin. - Refine and define your knowledge on the vascular anatomy of the face to stay safe when performing facial fillers to prevent dreaded complications including blindness and skin loss, as discussed by Dr. Rod Rohrich. - Define the limitations and safety areas for the use of laser and minimally invasive technology from laser to Radiofrequency to ultrasound technology to optimize results and maximize safety in the face and neck areas as discussed by Dr. Erez Dayan and Dr. Vic Ross"--